Pendidikan Multikultural dalam Bingkai Pemikiran Nasionalis Religius; Komparasi Konsep Abdurrahman Wahid dan Nurcholish Madjid - Setyazi, Gama; Subandi, Subandi; Abas, Erjati (Sekolah Tinggi Agam Islam Sumatera Medan, 2022)
This study aims to analyze the concept and comparison of the thoughts of Abdurrahman Wahid and Nurcholish Madjid regarding the concept of multicultural education from the perspective of religious nationalist thought. These two figures were chosen because of their popularity and their works as nationalist and religious figures in Indonesia. This research uses qualitative research methods, based on literature study. The data sources consist of two, namely primary which comes from the works of the two figures in terms of its relation to multiculturalism, and secondary which comes from journals or research findings. Abdurrahman Wahid is of the view that in a multicultural context, Islamic education must vary according to each culture. Diverse education does not deviate from the goal, but an effort to achieve educational goals through various ways. Nurholis Madjid is of the view that multiculturalism is not only co-existence but goes further than that, namely pro-existence. The phenomenon of multiculturalism in Islamic education is not only seen as a reality that is only allowed to exist, but is something that must be developed for the good of life.